The Erosional Signature of Drainage Divide Motion Along the Blue Ridge Escarpment. Issue 1 (3rd January 2023) - Stokes, Maya F.; Larsen, Isaac J.; Goldberg, Samuel L.; McCoy, Scott W.; Prince, Philip P.; Perron, J. Taylor
Abstract: The planform rearrangement of river basins is recognized as an important process for landscape evolution. The boundaries of river basins can shift either through gradual drainage divide migration or discrete river captures, but the methods for identifying these processes often rely on topographic evidence that remains otherwise untested. Moreover, efforts to understand the relative importance of either process are hampered by a lack of age constraints on river captures. We use 10 Be‐derived erosion rates to test whether, and how, divide motion is occurring at three locations along the Blue Ridge Escarpment in the Appalachian Mountains. In the Pee Dee River basin, we find that the escarpment is migrating inland up to 45 m/Myr, consistent with topographic evidence for gradual divide migration. In the Dan River basin, erosion rates support the topographic evidence for river capture, and we use a forward model of river incision to estimate that the capture likely occurred in the past 12.5 Myr. In the South Fork Roanoke River basin, where the presence of a knickzone has been interpreted as evidence that a river capture initiated a pulse of faster erosion, we instead measure nearly uniform tributary erosion rates above and within the mainstem knickzone. Simulations show that river incision into a more erodible layer of rock, with or without a river capture, could produce the observed topography and erosion rates in the South Fork Roanoke River. Our results show how multiple lines of evidence can illuminate the rates and mechanisms of river basin reorganization. Plain Language Summary: River basins are dynamic features; they can grow and shrink over time through the gradual movement of drainage divides across a landscape, a process called divide migration. Alternatively, a river channel can abruptly change its flow direction, and connect with a channel in another river basin, in an event called a river capture. Divide migration and river capture are often identified using clues extracted from topography. Such topographic evidence indicates that the Blue Ridge Escarpment in the Appalachian Mountains is migrating toward the continental interior. In this study, we measure erosion rates on either side of the escarpment to test whether Atlantic‐draining rivers are eroding faster than those perched at higher elevations on the Mississippi side. In two out of three study sites the erosion rates are consistent with the topographic evidence. In the third site, the erosion rates are inconsistent with the physical evidence for river capture. We pair our measurements with computational simulations to show that a river eroding into different rock types can produce topography that alters the signature of river capture. Our results show that the Blue Ridge Escarpment is in motion, but that topographic interpretations can be complicated by the presence of multiple rock types. Key Points: Paired erosion rates across the Blue Ridge Escarpment show that the escarpment is migrating up to 45 m/Myr toward the continental interior In the Dan River, nonuniform erosion rates and simulations suggest a river capture occurred in the last 12.5 Myr Uniform erosion rates in the Roanoke River show how incision into different rocks could obscure the topographic evidence of river capture